A prospective study of patients diagnosed with sarcoidosis: Factors - environmental exposure, health assessment, and genetic outlooks - Caruana, Louis B.; Redwine, Gerald D.; Rohde, Rodney E.; Russian, Chris J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
This original research is a directional study that determined the habits of individuals using four analyses to find statistical significance in the data collected from the surveys of 801 qualified of 1,340 individuals who agreed to participate. Results from the self-reported diagnosis of individuals affected by sarcoidosis produced seven statistically significant indicators of future research needed. The demographics revealed a significantly greater number of women and African-Americans participants than other minorities in the United States and suggested a sense of urgency to find a cure. Most important are the seven statistically significant findings that also gave credence to the researchers’ four subdiagnostic classifications. They are acute sarcoidosis (AS) and chronic sarcoidosis with limited dissemination (CSLD), while more severe cases include those with chronic sarcoidosis with full dissemination including cutaneous involvement (CSFDIC) and chronic sarcoidosis with neurosarcoidosis (CSN). The most severe sarcoidosis cases (CSN) were on the “most likely” side of every statistically significant category except drinking alcohol, and the “least likely” to participate in physical activities. Conversely, the least severe case of sarcoidosis (AS) was the opposite. The complete list of statistically significant areas was related to alcohol use, tobacco use, ciprofloxacin use, environmental exposure to metals (copper, iron), infectious diseases (candidiasis), genetics, and physical exercise. Statistically, the most crucial study needed; emerged from the Rh blood grouping of the participants.